Development of Modern Standards for Energy Efficiency of Industrial Enterprises within the European Union Policy - Zhao, Chen Pei; Gukasyan, Gurgen; Bezpalov, Valery; Prasolov, Valeriy (International Journal of Energy Economics and Policy, 2020)
This study is aimed at identifying the weaknesses and strengths of the mechanism for managing industrial energy efficiency (EE) under the EU policy. It is of interest not only for countries consuming energy raw materials but also for its suppliers, since they are to predict the situation on the markets and follow global trends in energy saving and environmental protection. Within the framework of the research, the methods of analogies and comparisons are used to determine the costs of switching industrial enterprises to the EE principles. The modeling method is applied to five companies in the EU, the USA, Russia, and China. By comparing the existing mechanism for EE regulating, excellent results for the EU industrial companies can be observed. They are characterized by the achievement of a high level of energy saving (10-12%) at low costs. For most US companies, an adequate level of potential energy conservation can be noticed. Russian industrial enterprises are characterized by low energy saving at a huge investment cost. For companies in China, favorable conditions are created to achieve efficient energy conservation, however, the cost for EE remains high. Keywords: costs, energy consumption, energy efficiency, energy management, energy saving. JEL Classifications: O1, Q4 DOI: https://doi.org/10.32479/ijeep.10160